Physiological role of silicon in radish seedlings under ammonium toxicity - Olivera Viciedo, Dilier [UNESP]; de Mello Prado, Renato [UNESP]; Lizcano Toledo, Rodolfo; Salas Aguilar, Dayami; dos Santos, Luiz Claudio Nascimento [UNESP]; Calero Hurtado, Alexander [UNESP]; Peña Calzada, Kolima [UNESP]; Betancourt Aguilar, Carmen (Wiley, 2020)
BACKGROUND: High concentrations of ammonium as the sole nitrogen source may result in physiological and nutritional disorders that can lead to reduced plant growth and toxicity. In this study, we hypothesized that ammonium toxicity in radish seedlings (Raphanus sativus L.) might be mitigated by the incorporation of silicon (Si) into applied nutrient solution. To examine this possibility, we conducted a hydroponic experiment to evaluate the effects of five concentrations of ammonium (1, 7.5, 15, 22.5, and 30 mmol L−1) on the photosynthesis, green color index, stomatal conductance, transpiration, instantaneous water-use efficiency, and biomass production of radish in the absence and presence (2 mmol L−1) of Si. The experimental design was a randomized block design based on a 2 × 5 factorial scheme with four replicates. RESULTS: The highest concentration of applied ammonium (30 mmol L−1) was found to reduce the photosynthesis, transpiration and total dry biomass of radish seedlings, independent of the presence of Si in the nutrient solution. However, at lower ammonium concentrations, the application of Si counteracted these detrimental effects, and facilitated the production of seedlings with increased photosynthesis, greater instantaneous water-use efficiency, and higher total dry biomass compared with the untreated plants (without Si). Transpiration and stomatal conductance were affected to lesser extents by the presence of Si. CONCLUSION: These findings indicate that the addition of Si to nutrient solutions could provide an effective means of alleviating the unfavorable effects induced by ammonium toxicity at concentrations of less than 30 mmol L−1. © 2020 Society of Chemical Industry.
Keywords: abiotic stress; hydroponics; nitrogen; Raphanus sativus L; tolerance; vegetable